Panning for gold, but finding helium: Discovery of the ultra-stripped supernova SN 2019wxt from gravitational-wave follow-up observations - Agudo I; Amati L; An T; Bauer FE; Benetti S; Bernardini MG; Beswick R; Bhirombhakdi K; de Boer T; Branchesi M; Brennan SJ; Brocato E; et al. (EDP SCIENCES S A, 2025)
We present the results from multi-wavelength observations of a transient discovered during an intensive follow-up campaign of S191213g, a gravitational wave (GW) event reported by the LIGO-Virgo Collaboration as a possible binary neutron star merger in a low latency search. This search yielded SN 2019wxt, a young transient in a galaxy whose sky position (in the 80% GW contour) and distance (~150 Mpc) were plausibly compatible with the localisation uncertainty of the GW event. Initially, the transient's tightly constrained age, its relatively faint peak magnitude (Mi ~ -16.7 mag), and the r-band decline rate of ~ 1 mag per 5 days appeared suggestive of a compact binary merger. However, SN 2019wxt spectroscopically resembled a type Ib supernova, and analysis of the optical-near-infrared evolution rapidly led to the conclusion that while it could not be associated with S191213g, it nevertheless represented an extreme outcome of stellar evolution. By modelling the light curve, we estimated an ejecta mass of only ~0.1 Mʘ, with 56Ni comprising ~20% of this. We were broadly able to reproduce its spectral evolution with a composition dominated by helium and oxygen, with trace amounts of calcium. We considered various progenitor channels that could give rise to the observed properties of SN 2019wxt and concluded that an ultra-stripped origin in a binary system is the most likely explanation. Disentangling genuine electromagnetic counterparts to GW events from transients such as SN 2019wxt soon after discovery is challenging: in a bid to characterise this level of contamination, we estimated the rate of events with a volumetric rate density comparable to that of SN 2019wxt and found that around one such event per week can occur within the typical GW localisation area of O4 alerts out to a luminosity distance of 500 Mpc, beyond which it would become fainter than the typical depth of current electromagnetic follow-up campaigns.